(untitled) (Cadernos de Sociomuseologia, 2024)
In this article we address a few questions that pervade the unclear relation between contemporary art and Sociomuseology. Mass culture and commercially oriented institutions may have created a distant gap between these two disciplines that became challenging to overcome in a social perspective – muffling conflictive memories and taking local narratives away from central debates. The identification of shared premisses between the socially engaged museums and politically positioned artists is attempt to place them under the Sociomuseological scope. By Analysing the short film Terra(In)Submissa by Kiluanji Kia Henda and Bruno Moraes Cabral, we base our argument on how poetical and political addressing of social tensions and traumas – such as the colonial past – are artistic manifestations that can be target of further research. Keywords English: Film; Art; Colonialism; Museology